Working with Faculty Writers - Eodice, Michele, 1957-; Geller, Anne Ellen, 1969- (Book collections on Project MUSE., 2013)
The imperative to write and to publish is a relatively new development in the history of academia, yet it is now a significant factor in the culture of higher education. This book takes a broad view of faculty writing support, advocating its value for tenure-track professors, adjuncts, senior scholars, and graduate students. The authors in this volume imagine productive campus writing support for faculty and future faculty that allows for insights about their own disciplinary writing and writing processes, as well as the development of fresh ideas about student writing. Contributors from a variety of institution types and perspectives consider who faculty writers are and who they may be in the future, reveal the range of locations and models of support for faculty writers, explore the ways these might be delivered and assessed, and consider the theoretical, philosophical, political, and pedagogical approaches to faculty writing support, as well as its relationship to student writing support.--description provided by publisher.